Perceived Burden of Multidrugs- Resistant Tuberculosis Patients And Their Family: A Systematic Review Of The Qualitative Literature - Sulistyono, R Endro; Wahyudi, Andri Setiya; Tristiana, Rr Dian (International Journal of Psychosocial Rehabilitation, 2020)
The incidence of Multiple Drugs Resistance Tuberculosis (MDR TB) is still very high. MDR TB treatments require a long period of care that could lead to an impact on MDR TB patients and their families. This study aims at reviewing and synthesizing the perceived burden of MDR TB patients and their families. A literature review was conducted through a search of four journal databases which found eight articles according to the inclusion criteria which were then identified, evaluated and synthesized. A thematic synthesis was conducted of the selected studies. This review identified four major themes related to the perceived burden by MDR TB patients and their family, namely; physical, psychological, social and financial burden. Understanding the difficulties and burdens experienced by MDR TB patients and their families is important in order to choose the appropriate intervention according to the problems that may arise due to MDR TB disease.